Socioeconomic position and self-harm among adolescents: a population-based cohort study in Stockholm, Sweden - Bereket T. Lodebo; Jette Möller; Jan-Olov Larsson; Karin Engström (BMC, 2017)
Abstract Background Understanding the association between parental socioeconomic position and self-harm in adolescence is crucial due to its substantial magnitude and associated inequality. Most previous studies have been either of cross-sectional nature or based solely on self-reports or hospital treated self-harm. The aim of this study is to determine the association between parental socioeconomic position and self-harm among adolescents with a specific focus on gender and severity of self-harm. Methods A total of 165,932 adolescents born 1988-1994 who lived in Stockholm at the age of 13 were followed in registers until they turned 18. Self-harm was defined as first time self-harm and severity of self-harm was defined as hospitalized or not. Socioeconomic position was defined by parental education and household income. Cox proportional hazards regression were used to estimate hazard ratios (HR) with 95% confidence intervals (CI). Results Analyses showed an association between parental socioeconomic position and self-harm. Among adolescents with parents with primary and secondary education compared to tertiary parental education the HR were 1.10 (95% CI 0.97-1.24) and 1.16 (95% CI 1.08-1.25) respectively. Compared to the highest income category, adolescents from the lower income categories were 1.08 (95% CI 0.97-1.22) to 1.19 (95% CI 1.07-1.33) times more likely to self-harm. In gender-stratified analyses, an association was found only among girls. Further, restriction to severe cases eliminated the association. Conclusions This study suggested that low parental socioeconomic position is associated with self-harm in adolescence, predominantly among girls. The desertion of an association among severe cases may be explained by differences in suicidal intent and underlying psychiatric diagnosis. Efforts to prevent self-harm should consider children with low parental socioeconomic position as a potential target group.